DEVELOPMENT OF ANDROID-BASED INTERACTIVE LEARNING MEDIA USING SMART APPS CREATOR (SAC) ON THERMOCHEMISTRY - Lokollo, Lita; Utubira, Yeslia; Pelu, Siti Harisa (Program Studi Pendidikan Kimia, FKIP, Universitas Pattimura (Chemistry Education Study Program, Faculty of Teacher Training and Educational Sciences, Pattimura University), 2025)
The integration of technology in learning allows the creation of various interactive media that can improve the effectiveness of learning. This study aims to develop interactive learning media based on Android using Smart Apps Creator on thermochemistry material. The development is carried out using the 4-D development model, which includes the stages of define, design, develop, and disseminate. However, this study is limited to the development stage. The research sample was students of Class XI MIA at SMA Negeri 31 Central Maluku. The instruments used were expert validation sheets and student response questionnaires. Data analysis was conducted descriptively quantitatively based on the assessment categories of media feasibility and practicality. The results of the study obtained showed that the average percentage of feasibility tests by material experts was 96% and media experts 94%, with a very feasible category, while the average percentage of practicality tests by students was 98%, with a very practical category. Thus, the interactive learning media based on Android using the Smart Apps Creator that was developed is very feasible and very practical to use in the chemistry learning process, especially thermochemistry materials.